Perlindungan Hukum bagi Saksi dalam Kasus Tindak Pidana Pencucian Uang di Indonesia - Adhalia Septia Saputri; Edi Saputra Hasibuan (Journal of Mandalika Literature, 2024)
Witness protection in money laundering (TPPU) cases is a crucial aspect in the law enforcement process, considering the complexity and risks faced by witnesses in disclosing this case. This research aims to analyze the legal protection provided to witnesses in TPPU cases in Indonesia, both in regulatory and implementation aspects. In this research, normative juridical methods are used with a statutory approach and case studies. The research results show that although there are regulations governing witness protection, such as Law no. 31 of 2014 concerning Witness and Victim Protection, its implementation still faces a number of obstacles, including a lack of coordination between institutions and minimal protection for witnesses from physical and psychological threats. This research also found that the role of the Witness and Victim Protection Agency (LPSK) in providing protection for witnesses is very important, but still requires strengthening, especially in handling money laundering cases involving organized crime syndicates. In conclusion, more comprehensive efforts are needed to provide legal protection for witnesses, including increasing the capacity of LPSK and harmonizing regulations related to witness protection in TPPU cas